Development Of Covid-19 Electronic Surveillance At Wates Regional General Hospital Kulon Progo - Slamet Ariyanto (Syntax Corporation Indonesia, 2022)
The purpose of the study is to build hospital-based COVID-19 electronic surveillance. The World Health Organization (WHO) designated the COVID-19 outbreak as a global pandemic in March 2020. One of the efforts to prevent and control the spread of COVID-19 is to conduct surveillance. Currently, the COVID-19 surveillance reporting system from the health service level to the center is still experiencing problems. Individual epidemiological investigation data has not been fully recorded on the surveillance system. As a result, the distribution of cases cannot be described properly. develop a COVID-19 electronic surveillance system at Wates Hospital. Method: mixed method exploratory sequential design research with a case study approach in the form of the development of surveillance systems. The study was conducted in four stages: identification of the needs of the COVID-19 electronic surveillance information system; design design and development of COVID-19 electronic surveillance; trials of developed systems; evaluation of development. the implementation of COVID-19 surveillance at Wates Hospital is guided by the surveillance guidelines of the Ministry of Health. The obstacles faced are the limited number of survilance officers, limited facilities, namely there is no special application of survilans for internal hospitals, and there is no good system so that the implementation is still manual, as a result of which the data produced is invalid. The development of electronic surveillance design can produce the information needed, has a high value of benefits, convenience, and acceptance from users. from the results of trials and evaluations of developed systems proven to provide ease value and benefit value, and get high acceptance from nurses as users, so that the COVID-19 surveillance electronic system developed is feasible to use